The Influence of Investment, Labor, and Government Expenditure on Economic Growth in South Sulawesi - Nursarfiqah; Naidah; Asdar (IECON: International Economics and Business Conference, 2025)
This study investigates the effect of investment, labor, and government expenditure on economic growth in South Sulawesi during the period 2014–2024. Using secondary data obtained from the Central Statistics Agency (BPS), the analysis applies multiple linear regression and t-tests with a panel data approach processed through SPSS 25. The dependent variable is regional economic growth measured by Gross Regional Domestic Product (GRDP) at constant prices, while the independent variables include realized investment, labor force participation, and government expenditure. The results reveal that investment shows a negative but insignificant effect on economic growth, indicating that capital inflows have not been effectively directed toward productive sectors that stimulate regional output. Labor exhibits a positive but statistically insignificant influence, suggesting that an increase in workforce quantity is not yet accompanied by sufficient productivity and skills development. Similarly, government expenditure demonstrates a negative and insignificant effect, implying inefficiencies in public spending allocation and a dominant share of non-productive expenditures. These findings highlight the structural challenges faced by South Sulawesi in translating investment, labor force expansion, and fiscal policy into tangible economic outcomes. The study contributes empirical evidence specific to the regional context and suggests that policymakers should focus on improving investment quality, enhancing human capital, and reallocating government spending toward productive sectors to achieve sustainable growth.